EKSISTENSI OBJEK WISATA ALAM AUA SARUMPUN DI KECAMATAN RAMBATAN KABUPATEN TANAH DATAR - Putri, Yohanna Widia; Edial, Helfia (JURNAL BUANA, 2024)
This research aims to determine the existence of the Aua Sarumpun natural tourist attraction in Rambatan Subdistrict, Tanah Datar District in terms of the aspect of natural tourism potential, the condition of tourist infrastructure, and the standardization criteria for natural tourism in Aua Sarumpun. This type of research is descriptive qualitative with the research location at the Aua Sarumpun Natural Tourism Object, Rambatan Subdistrict, Tanah Datar District. The results of the research show that the tourist attraction of Aua Sarumpun is in the form of natural views seeing the beauty of Lake Singkarak surrounded by mountains and hills, many photo spots which are often used as pre-wedding photo locations and are also often used as camping locations in terms of tourism potential. Based on the incomplete condition of infrastructure, such as the lack of a special place for souvenir shopping and road access to Aua Sarumpun which is still difficult to reach. Regarding the criteria for standardizing natural tourism according to SNI 8013:2014, five of the thirteen criteria for standardizing natural tourism in Aua Sarumpun have not been completely fulfilled.